Efektivitas dan Efisiensi Penggunaan Aplikasi Akuntansi UKM Terhadap Penyusunan Laporan Keuangan UMKM (Studi Kasus pada Usaha Mikro Kecil Menengah Sektor Kuliner di Kota Tegal) - Asyifa Maulida; Ida Farida; Anita Karunia (Politeknik Negeri Batam, 2021)
Akuntansi UKM application is an android-based financial application that can and is easy to use by micro, small and medium enterprises. The purpose of this research was to determine the effectiveness and efficiency level of used Akuntansi UKM application influence preparation of MSME financial report partially and simultaneously (case study on micro, small and medium enterprise culinary sector in Tegal City). Data collection techniques used were observation, interviews, literature study and questionnaires. The population in the research was MSMEs culinary sector in Tegal City. The sampling technique in this research used purposive sampling with a total of 28 respondents. The data analysis method used was descriptive statistical analysis, validity test, reliability test, class assumption test, multiple linear regression analysis and hypothesis test. The results of the t test analysis showed that the effectiveness variable had a significance value of 0,033 < alpha to 0,05. The variable efficiency had a significance value of 0.019 < alpha 0.05. The results of the F test analysis showed that the variable effectiveness and efficiency had a significance value of 0.002 < alpha 0.05. So, Ho is rejected and Ha is accepted which means effectiveness and efficiency are influential in the preparation of MSMEs' financial statements. The conclusion is the effectiveness and efficiency of using Akuntansi UKM application had influenced partially and simultaneously on preparation of MSME financial report on micro small medium enterprises culinary sector in Tegal City.